A formação de alunos leitores do mundo: do senso comum ao letramento científico - Santos, Olga Regina de Andrade Gil (2021)
The pendulum motion between common sense and science; the distance and convergence between Scientific Literacy and Scientific Read and Write ability; and the remote presence of the school amid the absence of the technologically isolated student are configured as elements of this research. Nurturing the school of potentiating strength for the formation of students substantially knowledgeable of the human civilization science and technology, past and present, and contribute to the awareness of the eternal becoming, have been, in my view, goals and continuous efforts of teachers, researchers, and education professionals. The knowledge involved in this reflection intends to pave the way so as to contribute to the school being studied and to public schools alike. The aim of the articulation between Scientific Literacy and the training of students who are readers of the world is to bring data of a first and modest look at the development of the scientific literacy skills of elementary school 8th graders and high school first-year and sophomore students. By modest look, we consider the restricted length of the research time, the stated objectives, and the limitations of the data sampling achieved during the pandemic. The center of attention of this study remained in the process of the initial formation of students for scientific literacy based on common sense. We focus on the formation of subjects who observe the world, read its codes, get involved with it, and understand its functioning. The focal point of this work is the verification of the multiple reading skills, in the search for understanding the meaning of information by the students. Reading here is understood not just as the identification of printed matter, but as an ability to verify the essence of things and the events of the world. The research has shown that the subjects, equipped with their understanding and knowledge, even if pre-scientific, make use of criticism for themselves and the other; they look at the world with the astonishment necessary for the emergence of senses; they display traits that allow them to understand the care and responsibility for human life -their own and that of others -and for the planet. Students accomplish all this during a pandemic context (2020-2021), experiencing intermittent education, immersed in the fear of contamination, coping with the insecurities of the society about its future, with low access to technological tools and, unfavorably, with questions coming from social media that cast doubt on the validity of science